2019
DOI: 10.1177/0310057x18811725
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of different modes of pneumatic compression on muscle tissue oxygenation: An intraparticipant, randomised, controlled volunteer study

Abstract: Intermittent pneumatic compression (IPC) to the lower limbs is widely used as a mechanical means to prevent deep vein thrombosis in hospitalised patients. Due to a theoretical concern about impairing blood flow, thromboembolicdeterrent stockings and IPC are considered contraindicated for patients with peripheral vascular diseases by some clinicians. This study assessed whether IPC would alter peripheral limb muscle tissue oxygenation (StO 2 ), and whether such changes were different during 10 minutes of sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…In healthy people, IPC led to a greater increase in flow velocity and volume flow when compared with that shown in a simple leg elevation [10] . Despite concerns that IPC may cause blood vessel obstruction, which could in turn reduce blood flow, a recent study examining peripheral limb muscle tissue oxygenation after applying IPC in healthy volunteers found that both single chamber and multichamber sequential compression increased limb muscle oxygenation [11] …”
Section: Discussionmentioning
confidence: 99%
“…In healthy people, IPC led to a greater increase in flow velocity and volume flow when compared with that shown in a simple leg elevation [10] . Despite concerns that IPC may cause blood vessel obstruction, which could in turn reduce blood flow, a recent study examining peripheral limb muscle tissue oxygenation after applying IPC in healthy volunteers found that both single chamber and multichamber sequential compression increased limb muscle oxygenation [11] …”
Section: Discussionmentioning
confidence: 99%
“…102,103 A just published investigation reported how both sequential and single-compartment compressions are able to increase tissue oxygenation, with a significantly higher effect using the multi-chamber device. 104 On the thrombo-embolism side, in 2016 Cochrane 105 analysis showed a benefit in adding IPC to pharmacological thrombo-prophylaxis in high-risk trauma and surgical patients, while, in 2019, New England Journal of Medicine underlined no significant benefit in adding IPC in critically ill patients already covered by drugs for venous thrombo-prophylaxis. 106…”
Section: Significant New Data Related To the Meeting Discussionmentioning
confidence: 99%
“…A just published investigation reported how both sequential and single-compartment compressions are able to increase tissue oxygenation, with a significantly higher effect using the multi-chamber device. 104…”
Section: Bandaging Adjustable Compression Wraps Intermittent Pnementioning
confidence: 99%
“…It also causes the largest increase in venous outflow in the foot and calf [ 44 ]. The risk for blood vessel obstruction with IPC use has been reported, but the application of IPC to healthy subjects increases the oxygenation of muscle cells in the lower limb [ 45 ]. Like MCS, there are still no international consensus pressure values or modes in IPC.…”
Section: Discussionmentioning
confidence: 99%